Psychologists’ Experience and Management of Zoom Fatigue - Cornthwaite, Kelsey (Auckland University of Technology, 2022)
The COVID-19 pandemic has resulted in drastic changes to daily routines for psychologists. Driven by the need for remote and flexible ways of providing clinical services while keeping in line with stay-at-home orders, the pandemic has resulted in a rise in the use of videoconferencing tools for online therapy. The increasing use of videoconferencing has raised concerns around reports of feeling tired and exhausted following virtual meetings, termed "Zoom fatigue”. The use of videoconferences in therapy is likely to continue beyond the pandemic, yet limited literature has examined the experiences of Zoom fatigue from psychologists’ perspectives. Understanding how Zoom fatigue may be experienced and managed can provide strategies for more appropriate use of videoconferences and allow for more effective and productive working environments. The current study utilises a qualitative descriptive approach to explore psychologists’ experiences and management of Zoom fatigue. Reflexive thematic analysis of six semi-structured interviews with New Zealand registered psychologists revealed themes that the experience of Zoom fatigue is related to mental, emotional and physical fatigue. Zoom fatigue may also be understood in relation to experiences of technical challenges, stressors of working from home, and difficulties cultivating a therapeutic relationship with clients. The findings of this study suggest that despite the reported challenges of Zoom fatigue, there are effective methods to mitigate the experiences of Zoom fatigue where future uses of videoconferences in therapy can be successfully implemented if it is applied appropriately.